2010
DOI: 10.1590/s0103-84782010005000167
|View full text |Cite
|
Sign up to set email alerts
|

Frequência e intensidade de poda em pomar jovem de laranjeiras 'Valência' sob manejo orgânico

Abstract: RESUMO Este trabalho teve por objetivo avaliar o efeito da frequência e intensidade de poda sobre a produção e qualidade dos frutos da laranjeira 'Valência

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
1
2
0
5
Order By: Relevance
“…However, skirting tests performed with prepruners have shown that the overall production of the tree is not affected, while mechanical harvesting is facilitated, problems with soil fungus are reduced and tree microclimate is affected (El-Zeftawi, 1976;Morales & Davies, 2000;Sauls, 2008). Similar results were obtained by Santarosa et al (2010), who tested pruning combined with thinning to regulate size and bearing in orange trees. According to Sauls (2008), bearing can be controlled with mechanical pruning, since using this technique after a year of low yield will potentially become the precursor of a highly productive year.…”
supporting
confidence: 80%
“…However, skirting tests performed with prepruners have shown that the overall production of the tree is not affected, while mechanical harvesting is facilitated, problems with soil fungus are reduced and tree microclimate is affected (El-Zeftawi, 1976;Morales & Davies, 2000;Sauls, 2008). Similar results were obtained by Santarosa et al (2010), who tested pruning combined with thinning to regulate size and bearing in orange trees. According to Sauls (2008), bearing can be controlled with mechanical pruning, since using this technique after a year of low yield will potentially become the precursor of a highly productive year.…”
supporting
confidence: 80%
“…Also, the frequency of green pruning showed no interaction with nitrogen fertilization (Tables 1 and 2). Green pruning recommended by peach integrated production could be used for other purposes, such as to improve the luminosity and aeration of the canopy, to control excessive vegetative growth, to reduce the incidence of diseases and to facilitate cultural practices (Tutida et al 2007;Tratch et al 2010;Santarosa et al 2013). However, the use of higher intensity of green pruning (CGP) should not be recommended if the purpose was only to improve the quality of the fruit, due to the costs for its implementation.…”
Section: Resultsmentioning
confidence: 99%
“…Nas safras de 2006 e 2007, também não houver diferenças das podas em relação à Testemunha, exceto para poda trienal de 30%, que foi superior aos demais na safra de 2007, correspondendo à terceira safra após sua aplicação. Ao contrário do observado em experimentos realizados por Santarosa et al (2010), em pomares submetidos ao manejo orgânico, onde se verificou uma redução da produção de frutos no ano subsequente à realização da poda, tanto com aplicação de poda leves de 15% quanto de podas severas de 30%.…”
Section: Resultsunclassified
“…Estes fatores fazem da poda uma prática importante tanto para a produção quanto para a qualidade de frutos, principalmente em pomares de citros cujos frutos se destinam ao consumo in natura (SARTORI et al, 2007), sendo considerada uma ferramenta auxiliar para o manejo do pomar, facilitando também os tratos culturais, como tratamentos fitossanitários e a colheita. Entretanto, alguns trabalhos demonstram que a poda não interfere na qualidade dos frutos de tangerineiras (MEDEIROS et al, 2009), nem de laranjeiras com menos de sete anos de idade, conduzidas em sistemas orgânicos de produção (SANTAROSA et al, 2010).…”
Section: Introductionunclassified
See 1 more Smart Citation